Technical change and efficiency in Irish agriculture - O'Neill, Suzanne; Matthews, Alan (Economic & Social Studies, 2001)
This paper calculates average technical efficiency levels and rates of technical change for Irish agriculture using an unbalanced panel of 2,603 farms drawn from the Irish National Farm Survey over the period 1984 to 1998. An average technical efficiency level of between 65 and 70 per cent with a slight upward trend over the period was found. The efficiency of individual farms is positively associated with the size of the farm household, the ratio of debt to assets and the farmer?s age, and negatively related to being located in the West of Ireland, having an off-farm job and size of farm. Technical progress is observed at an unweighted rate of approximately 0.9 per cent and a weighted rate of 2.1 per cent per annum over the 1984-98 period. There is evidence that this rate of growth has been slowing over time. Technical progress was considerably faster on farms in the East of the country compared to Western farms, on larger farms compared to smaller ones, and on dairy and tillage farms compared to cattle and sheep farms.
Keywords: Technical change; Agriculture; Efficiency; Ireland